Optimization of Zakat Collection at the National Amil Zakat Agency (BAZNAS) of Malang Regency - Romadlon Chotib; Nur Cholilah (Islamic Studies in the World, 2024)
Background. The potential for zakat in Indonesia is very high and has become an important instrument in alleviating poverty, although its realization is still far from its potential. Accurate collection and distribution of zakat can help ease the burden on other Muslim brothers and sisters who are economically disadvantaged, because it is actually a shared task in overcoming poverty and economic downturn. Purpose. The aim of this research is to analyze and identify factors that influence the optimization of zakat collection at the Malang Regency National Zakat Amil Agency (BAZNAS). This research aims to develop an effective strategy in increasing public awareness and participation in paying zakat, as well as improving the zakat management mechanism by BAZNAS to make it more transparent, accountable and efficient. Thus, it is hoped that the results of this research can provide concrete recommendations to increase the amount of zakat collected and ensure proper distribution to those in need. Method. This research is qualitative research where the data is displayed in a natural state, the data is not processed and is not displayed in numbers or numbers, based on studies, books and books which are the basis for taking the data theory used in this research. Primary data is data collected directly by researchers, either through interviews or reports in the form of unofficial documents which will then be processed by researchers. Results. The results of this research are the policy for collecting zakat funds at BAZNAS MALANG Regency and distributing zakat funds at BAZNAS Malang Regency. Conclusion. Zakat, meaning 'blessing, clean, good,' must be issued by every Muslim and distributed according to Islamic law, according to Law no. 23 of 2011. BAZNAS Malang Regency optimizes zakat collection through socialization, promotional media, and coordination with the Zakat Collection Unit (UPZ). The collected zakat is distributed through five programs: Healthy Malang, Smart Malang, Careful Malang, Prosperous Malang, and Taqwa Malang, to improve the welfare of zakat recipients